A socio-historical reading of the French Nuclear Tests in the Algerian Sahara - Abdelouahab, Yahiaoui (The International tax journal, 2026)
This paper examines the French nuclear tests conducted in the Algerian Sahara from a historical and sociological perspective, with a particular focus on their political, economic, social, psychological, environmental, and cultural dimensions. The study analyzes manifestations of French imperial-capitalist domination and its repercussions on local populations, including radioactive pollution, social and psychological transformations, and the restructuring of local economic systems. The paper also highlights the efforts of the Algerian state after independence in developing scientific research, strengthening environmental monitoring, and promoting community participation in order to address the consequences of this nuclear legacy. In addition, it discusses the role of media and culture in documenting these tests and raising public awareness, alongside international comparisons that situate these experiments within a broader global context. The study concludes by drawing a set of strategic lessons related to the protection of human rights, the strengthening of national sovereignty, and the promotion of sustainable development pathways, while seeking to transform the nuclear legacy from a source of threat into a field of learning and future benefit.